Enhancing parental involvement in Early Childhood Development Centres - Bipath, K.; Bishop-Kapp, D. (South African Journal of Higher Education, 2025)
The discontinuation of government subsidies led to ECD centre privatisation and the rise of community-driven ECD ones, raising concerns about teaching quality and staff qualifications. The study aimed to create a framework for enhancing parental involvement by incorporating insights from both parents and teachers. Theoretical perspectives by Goodall and Montgomery, Vincent, and Bryk highlighted parenting’s significance, socio-economic influence on parental agency, and the need for trust between parents and teachers. The researchers selected two early childhood development centres and asked teachers and parents to participate. Qualitative research methods, including narrative inquiry, vignettes, participatory reflection and action research, and thematic analysis, were used to gather and analyse data from parents and teachers. The findings informed the development of the author’s Framework for the Enhancement of Parental Involvement in Childhood (EPIC), incorporating the key elements identified in previous research, namely parental agency, relational trust, and parental involvement. Parental agency is a characteristic that can be strengthened when teachers provide encouragement and insight into how to engage the child in a meaningful and developmentally appropriate manner. This research led to the design of a framework for enhancing parental involvement by considering the perspectives of both parents and teachers. It is particularly applicable to the pre-primary and foundation phases of preparatory schools where parental involvement is significant. It also benefits the training of prospective teachers, especially those specialising in Early Childhood Education.